2022
DOI: 10.1155/2022/4685288
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Alterations Associated with Age of Patients with Nephropathia Epidemica

Abstract: Nephropathia epidemica (NE) is a zoonotic disease caused by hantaviruses transmitted from rodents, endemic in the Republic of Tatarstan, Russia. The disease presents clinically with mild, moderate, and severe forms, and time-dependent febrile, oliguric, and polyuric stages of the disease are also recognized. The patient’s cytokine responses have been suggested to play a central role in disease pathogenesis; however, little is known about the different patterns of cytokine expression in NE in cohorts of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…These findings suggest that including rosuvastatin as a supplementary treatment could improve NE symptoms. We believe that the effect of rosuvastatin was linked to its anti-inflammatory effects which have been demonstrated in vitro [ 32 ] and in vivo [ 33 , 34 ]. It has been suggested that the inhibitory effect of statins on inflammation is due to the reduced production of proinflammatory cytokines [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that including rosuvastatin as a supplementary treatment could improve NE symptoms. We believe that the effect of rosuvastatin was linked to its anti-inflammatory effects which have been demonstrated in vitro [ 32 ] and in vivo [ 33 , 34 ]. It has been suggested that the inhibitory effect of statins on inflammation is due to the reduced production of proinflammatory cytokines [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the effect of rosuvastatin was linked to its anti-inflammatory effects which have been demonstrated in vitro [ 32 ] and in vivo [ 33 , 34 ]. It has been suggested that the inhibitory effect of statins on inflammation is due to the reduced production of proinflammatory cytokines [ 32 , 35 ]. In this study, rosuvastatin reduced the serum levels of only a few proinflammatory cytokines, namely IL-1α, IL-1β, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective PUUV patient cohort study aimed to identify biomarkers associated with more severe disease in terms of platelet count and kidney injury. IL-18 is an important pro-inflammatory cytokine often found to be upregulated in PUUV patients compared to healthy controls, indicating a role in pathogenesis [ 12 , 13 , 14 , 15 ]. In the current study, IL-18 was significantly higher in patients in the low platelet group.…”
Section: Discussionmentioning
confidence: 99%
“…Hantavirus infection induces a cytokine storm activating a plethora of immunopathological processes. Age‐ and gender‐dependent differences were described in the immune response against hantavirus infection 10–12 . Several cytokines and markers of cellular damage have been identified to be associated with severity of clinical course in hantavirus infection 7,13–23 …”
Section: Introductionmentioning
confidence: 99%
“…Age-and gender-dependent differences were described in the immune response against hantavirus infection. [10][11][12] Several cytokines and markers of cellular damage have been identified to be associated with severity of clinical course in hantavirus infection. 7,[13][14][15][16][17][18][19][20][21][22][23] The balanced host immune reaction determines the severity of disease by eradication of the invading pathogen but avoiding detrimental tissue damage due to poorly controlled immune activation.…”
mentioning
confidence: 99%